Perancangan Bejana Tekan Dalam Aspek Kekuatan Mekanik Berdasarkan Code Standard ASME VII DIV 1 Studi Kasus Crude OilStripper Pada Central Processing Facilities Banyu Urip Project Cepu - Yudhi Chandra Dwiaji (Journal of Applied Mechanical Engineering and Renewable Energy, 2023)
The shell, head, nozzle, and supports of pressure vessels are based on the results of manual calculations and are widely used in petrochemical plants, energy (power plants), oil and gas (oil and gas plants), and the industrial sector as a whole. The objective of this analysis is to comprehend the code that is used in the vertical pressure vessel design calculations so that they can be utilized in the field. The purpose, aesthetic value, and working environment of the pressure vessel must all be taken into consideration when designing its shape. Design pressure, the ship's dead weight, wind loads, earthquake-related loads, and combined loads are among the ship's loads. The ASME Part VIII Division I code standards are utilized when designing pressure vessels. Microsoft Excel software is used to calculate the shell thickness, head, nozzle, and support, or manual calculation is used. The thicknesses of the shell, head, nozzle, and support vary according to the results of the manual calculations. Shell thickness 1: 13mm, shell thickness 2: 16mm, shell thickness 3: 16mm, top head thickness: 13mm, bot head thickness: 16mm, nozzle thickness: 6mm, skirt thickness: 22mm.